2014
DOI: 10.1016/j.jacr.2014.03.022
|View full text |Cite
|
Sign up to set email alerts
|

Geographic Access to Breast Imaging for US Women

Abstract: Background The breast imaging modalities of mammography, ultrasound, and magnetic resonance imaging (MRI) are widely used for screening, diagnosis, treatment, and surveillance of breast cancer. Geographic access to breast imaging modalities is not known at a national level overall or for population subgroups. Methods A retrospective study of 2004-2008 Medicare claims data to identify ZIP codes in which breast imaging occurred, and data were mapped. We estimated travel times to each modality for 215,798 censu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
53
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(58 citation statements)
references
References 27 publications
3
53
2
Order By: Relevance
“…Rural communities often are less racially and ethnically diverse than urban areas ( 1 ), have worse health outcomes ( 2 , 3 ), and have less access to care ( 4 ). Although less heterogeneous than urban areas, the demographic composition of rural communities is becoming more diverse, driven in large part by populations that have not historically lived in rural communities ( 1 , 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…Rural communities often are less racially and ethnically diverse than urban areas ( 1 ), have worse health outcomes ( 2 , 3 ), and have less access to care ( 4 ). Although less heterogeneous than urban areas, the demographic composition of rural communities is becoming more diverse, driven in large part by populations that have not historically lived in rural communities ( 1 , 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…described rapid expansion of breast pMRI use in the United States, 4,5,[19][20][21] ranging from a 3-4 to 20-fold 5 increase in the past 10 years. To our knowledge, there are no large-scale studies demonstrating the potential associated downstream negative consequences associated with pMRI in routine clinical practice.…”
mentioning
confidence: 99%
“…Next, we found geographic variations in costs by comparing urban, rural, and critical access hospital status as defined by the CMS [4]. Previous studies have suggested that access to care for advanced imaging is a concern for rural and critical access hospitals [16,17,22], which may be directly attributable to the relatively high cost of purchasing and maintaining advanced imaging modalities in low-utilization areas [26]. Urban-rural discrepancies in the orthopaedic workforce have been noted previously, with fewer orthopaedic surgeons practicing in rural areas of the country which might affect access to quality orthopaedic care in these areas [11].…”
Section: Discussionmentioning
confidence: 99%